Remarks on the name of the Carians - Diether Schürr (Gephyra, 2018)
Kr̥ka-, the Old Persian name for the Carians, has nothing to do with Kar(a)kiša and Karkiya, countries mentioned in Hittite sources. The meaning of Old Persian *kr̥ka- is ‘rooster’, and the Carians were called so because of the crest on their helmets (Plutarch), but probably also because of their similar name, attested without -ka- in other languages.